Creative use of musical and pedagogical work of Chinese educators on the basis of integrated education in Ukrainian universities - Yue, Wu; Zelenska, Liudmyla (Professional Art Education, 2024)
The article presents materials that reveal a modern approach to the implementation of the ideas of integrated learning in Ukrainian pedagogical universities at the faculties of arts. Methods and methodology. The article uses the method of scientific research and practical methods of studying the results of creative work with foreign applicants for higher art education during classroom lessons and practice at school. Scientific novelty. An attempt is made to determine the main problems of training Chinese educators for practical work with students on the basis of an integrated approach in music education and areas of work with foreign students during their studies at Ukrainian universities in the new list of specialties 014.13 «Secondary education. Art. Musical art» using the example of the academic discipline «Voice performance». Results. A theoretical and methodological basis for training Chinese educators in the new requirements of the specialty 014.13 (Secondary education. Art. Musical art). The role of Musical Art as one of the dominant lines of the integrated art course in school practice based on the modular programs of the New Ukrainian School was analyzed. A comparative analysis of the selection of educational material during the period of pedagogical practice by applicants based on two schools in Ukraine and the PRC was carried out in order to ensure its compliance with three levels of integration (local, block, complex). It was proposed to use the “language methodology” to train future music and pedagogical workers from the PRC in the process of classes on “Voice Performance”, which includes work on vocal works at three stages of their mastery. Accordingly, the content of work with applicants-vocalists on works of the concert program of different speech cultures was clarified. Levels for the formation of integrated knowledge of applicants during the mastery of concert works in accordance with their thematic and block content were determined. Conclusions. The integrated essence of musical texts during the perception of program music by students was revealed. An example of vocal work on a piece from the musical by R. Rogers “Edelweiss” is provided from the standpoint of its creative mastery and the possibility of using it in further practical work with students on the principles of integrated learning. It is proven that for the effective training of Chinese educators in the specialty 014.13 “Secondary Education. Art. Musical Art” at the faculties of arts of Ukrainian pedagogical universities, one of the academic disciplines can be chosen as an “integrating core” and the learning process can be organized taking into account the requirements of school music education on the basis of integrated learning. An example of interdisciplinary integration can be the academic discipline “Voice Performance”, which interacts not only with the professional educational components of the professional training programs of future teachers of musical art, but also involves applicants in “complexity” in obtaining integrated knowledge of other subject areas.